1999
DOI: 10.1200/jco.1999.17.6.1710
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of BAG-1 in Invasive Breast Carcinomas

Abstract: BAG-1 is overexpressed in the majority of invasive breast carcinomas. Although BAG-1 did not correlate with conventional prognostic factors, its overexpression, especially the nuclear expression, may be associated with a shorter disease-free and overall survival. Our preliminary data strongly indicate that further investigation is warranted to define the role of BAG-1 as an independent prognostic factor in patients with newly diagnosed breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 31 publications
7
65
2
Order By: Relevance
“…We recently conducted a retrospective pilot study of BAG-1 expression in 140 patients with invasive breast cancer (53). BAG-1 expression was detected by a commercially available polyclonal antibody that did not cross-react with background proteins or other BAG-1-like proteins, such as BAG-1, BAG-3, and BAG-4.…”
Section: Bag-1 In the Prognosis Of Breast Carcinomamentioning
confidence: 99%
“…We recently conducted a retrospective pilot study of BAG-1 expression in 140 patients with invasive breast cancer (53). BAG-1 expression was detected by a commercially available polyclonal antibody that did not cross-react with background proteins or other BAG-1-like proteins, such as BAG-1, BAG-3, and BAG-4.…”
Section: Bag-1 In the Prognosis Of Breast Carcinomamentioning
confidence: 99%
“…A strong relationship between nuclear BAG-1 expression and tumour grade/differentiation has been identified in two studies, with relatively high levels of nuclear BAG-1 expression in low grade tumours (Tang et al, 1999;Townsend et al, 2002). By contrast, Turner et al (2001) reported no correlation between tumour grade and BAG-1 expression.…”
Section: Bag-1 and Breast Cancermentioning
confidence: 94%
“…This is particularly interesting since it was suggested that this might provide a means by which node negative patients with a relatively poorer prognosis could be selected for further adjuvant therapies, and conversely enable better prognosis node negative patients to avoid such therapies with their concomitant side effects. This exciting finding awaits confirmation (Tang et al, 1999;Townsend et al, 2002). Tang et al (1999) found no correlations between BAG-1 expression and outcome in univariate analysis and conversely reported that increased BAG-1 expression correlated with decreased disease free and overall survival in a multivariate analysis controlled for tumour differentiation.…”
Section: Bag-1 and Breast Cancermentioning
confidence: 96%
See 2 more Smart Citations